Analisis Fonetik dan Fonemik Bahasa Edang Masyarakat Desa Mahal II Kedang Omesuri Lembata - Yoakim Yolanda Mario Leu (Departement of Mathematics Education, 2024)
Phonology is a field of linguistics that provides a focus on the language system, especially language sounds or the science of how a sound occurs. Language sounds are produced by the human speech apparatus due to vibrations which are then exhaled through the nasal cavity or mouth. Wiyayanto (2023:5-6) states that phonology is a branch of linguistics that studies the sound system of human language which involves several important elements, namely sounds or fonts. The sound of these words has its own characteristics, one of which is the Kedang language spoken by the people of Mahal II Village. The Kedang language is spoken by people who live in two sub-districts in Lembata Regency, namely Omesuri sub-district and Buyasuri sub-district. This research aims to provide a descriptive picture of the phonetic and phonemic aspects of the Edang language used or spoken by the Mahal II Village Community. It is hoped that this study can provide benefits and contribute data related to the branch of phonology. Apart from that, it can provide an idea for the community and other institutions to pay more attention to the study of language sounds, especially regional languages. This research method is qualitative descriptive research. This research aims to describe the phonetic and phonemic forms found in the Edang language spoken by the Mahal II Village Community. The approach used in this research is a qualitative approach. The Kedang language has a phonetic aspect consisting of vowels and consonants. There are 17 variants of vowel sounds in the Kedang language used by the Mahal II Village Community, namely /a/, /e/, /i/, /u/, /o/, /:uˀ/, /:a/, /:e/, /:i/, /:u/, /:o/, /:iˀ/, /aˀ/, /eˀ/, /iˀ/, /uˀ/, and /oˀ/. Meanwhile, there are 11 variants of consonant sounds, namely /b/, /p/, /m/, /w/, /d/, /t/, /l/, /n/, /r/, and /s/ . Meanwhile, the phonemics of the Kedang language used by the people of Mahal II Village are vowels and consonants. Vowel Phonemic Sounds consist of /a/ and /:a/, /i/ and /u/, /eˀ/ and /u/, and aˀ and [oˀ]. Meanwhile, consonant sounds consist of /p/ and /t/, /l/ and /p/, /m/ and /w/, and /d/ and /t/.